PARADIGMA ‘TEOLOGI FEMINIS’ YANG TIDAK RELEVAN DENGAN KETETAPAN TUHAN: Suatu Respon Empiris Dari Perspektif Injili - Youke L. Singal; Radjiman Sirait (Sekolah Tinggi Teologi Moriah, 2022)
The presence of feminist theology has shaken both the church and the general public. They assume that many men occupy positions and positions that are